2016
DOI: 10.1159/000449373
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Function, <b><i>APOE</i></b> Gene Polymorphisms, and Thyroid Status Associations in Postmenopausal Women in Poland

Abstract: Background: The objective of the study was to analyze a potential association between cognitive functions and thyroid status in postmenopausal women with different polymorphisms of the apolipoprotein E gene (APOE). Methods: The examined population included 402 postmenopausal women from south-eastern Poland. The evaluation of cognitive functions was made with the use of the diagnostic Central Nervous System-Vital Signs equipment (Polish version). Multiplex polymerase chain reactions were performed to assess APO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…In light of the well-acknowledged association between the ε4 allele and AD, our findings are supported by a prior study illustrating significant impairment in SM relative to EM among AD patients [ 35 ]. Another recent study also revealed potential interplay between the ε4 allele and TSH regarding cognitive function as implied in our study [ 36 ].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In light of the well-acknowledged association between the ε4 allele and AD, our findings are supported by a prior study illustrating significant impairment in SM relative to EM among AD patients [ 35 ]. Another recent study also revealed potential interplay between the ε4 allele and TSH regarding cognitive function as implied in our study [ 36 ].…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, thyroid hormones are thought to not only regulate the precursor of β-amyloid protein, but also influence the brain metabolism and the modulation of APOE gene expression in the brain [ 21 , 37 ]. Both APOE and alteration of TSH is also believed to influence hyperphosphorylation of tau protein involved in the pathogenesis of AD [ 14 , 36 ], which sheds additional light on likelihoods of the interaction of these parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Common variants in dozens of genes are associated with late-onset AD[57]. The APOE ε4 allele has the strongest and most consistent evidence for association with increased risk of both sporadic and familial AD[6,7], and has been independently associated with cognitive function[8,9] and other dementing disorders[10,11]. Variants within genes causing other dementing disorders have also been associated with AD risk, including MAPT [12–14], PRNP [15], GRN [14], and TREM2 [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, although we confirmed that our participants had no crucial metabolic problems, it is possible that other factors or metabolic pathways influenced the effects of thyroid hormones on cognitive function we observed. Finally, although sex is regarded to be an important parameter in estimating the risk of AD or thyroid disease ( 42 ), we did not perform analyses according to sex, due to the relatively small number of men in our sample. Nevertheless, our findings provide important insights that help our understanding of the associations between thyroid hormones, cognitive performance, and APOE genotypes in patients with SCD.…”
Section: Discussionmentioning
confidence: 99%